Analisis Indeks Koneksi Pasar dan Distribusi Margin Pada Lembaga-Lembaga Pemasaran Ternak Sapi Potong di Kabupaten Kupang Nusa Tenggara Timur Indonesia - Yakob Robert Noach; Matheos Filipus Lalus (Fakultas Pertanian, Universitas Timor, 2020)
The activities of institutions involved in cattle marketing in Kupang-District East Nusa Tenggara include: purchasing, transportation, sorting, standardization and assessment, and so on. This research was conducted by survey method. The results of this study: IMC between the price of cattle at the farmer level and midlemen of 1.0040; between farmers and inter island traders 1,0048; between midlemen and inter-island traders 1.0714. Means that in the short term the price of beef cattle in the market has not been perfectly integrated. The farmers’ share is fair enough, while the whole cattle market in this region is imperectly integrated. The average of farmers’ share in the study area is 75.95%. Marketing margin is 62.17%; profit margin is 66.71%. The biggest profit margin received by midlemen is 60.70%, inter-island traders is 29.30%. There was disparity in distribution of marketing margins between midlemen and inter-island traders, where for midlemen 88.57% and for inter-island traders 48.33%.